A novel waveguide design that produces an elongated laser beam output for soft tissue ablation - Jaafar, Nurul Syahirah Aziz; Sepeai, Suhaila; Lim, Kok Sing; Zaini, Muhammad Khairol Annuar; Ahmad, Harith; Tan, Guan Hee (Elsevier, 2018)
In this work, we have fabricated and experimentally demonstrated a purpose-built 365 μm optical fibre device that produces an elongated laser beam output for efficient tissue ablation. The proposed fibre device has several advantages and potential for application in surgery. The off-axis firing beam from the fibre lowers the risk of past-pointing injury as compared to forward-firing laser fibres. A pulsed Holmium:YAG (Ho:YAG) laser at a wavelength of 2.1 μm at a repetition rate of 6 Hz was used in this experiment. The fibre was angle-polished at ∼25° to create a deviated beam that resulted in a longer ablation length ∼1 cm; it was five times longer than the forward-firing laser output and had sufficient energy intensity to perform an ablation rate of 7.7 μm per pulse. Fresh squid (Cephalopod Theutida) was used as the biological tissue to determine the ablation length and crater. The threshold radiant exposure, Φth for tissue ablation was estimated to be 1.84 J/cm2 and the effective divergence angle was ∼24° by using the highest pulsed energy of 1.8 J.